8.7k views
1 vote
X-7(x-2)=10x+9-x
i need the answer asap pls

1 Answer

4 votes

Explanation:

x−7(x−2)=10x+9−x

Step 1: Simplify both sides of the equation.

x−7(x−2)=10x+9−x

x+(−7)(x)+(−7)(−2)=10x+9+−x(Distribute)

x+−7x+14=10x+9+−x

(x+−7x)+(14)=(10x+−x)+(9)(Combine Like Terms)

−6x+14=9x+9

−6x+14=9x+9

Step 2: Subtract 9x from both sides.

−6x+14−9x=9x+9−9x

−15x+14=9

Step 3: Subtract 14 from both sides.

−15x+14−14=9−14

−15x=−5

Step 4: Divide both sides by -15.

−15x−15=−5−15

x=13

Answer:

x=13

User Matiascelasco
by
5.5k points